Nutritional characterization of various classes of Egyptian beef luncheon - Maky, Mohamed Abdelfattah; Sadek, Mustafa; Shanab, Obeid; Mahmoud, Hala Abdel Mohsen; Rehan, Ibrahim Farag (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: The present work was conducted to investigate the nutritional profile of the highly consumed beef luncheon in Egypt. Besides, the potential health hazards associated with the consumption of luncheon were highlighted. Material and methods: A total of 60 beef luncheon samples were collected from Egyptian markets. They were classified into three classes: A, B, and C based on their prices. The collected samples were examined for their chemical composition by determining moisture, protein, fat, ash, carbohydrate, and energy percentage. The contents of trace elements were also investigated. Results: The obtained findings showed a comprehensive dissimilarity in the chemical composition. According to the fresh weight base, moisture, protein, fat, ash, and carbohydrate fluctuated from 56.97 to 64.52, 3.50 to 16.10, 4.73 to 13.39, 3.30 to 3.51, and 11.32 to 27.44% w/w, respectively. The highest price class A Egyptian beef luncheon had more accepted nutritive value and dietary energy content. All the examined classes were low in calcium, potassium, zinc, and magnesium. The target hazard quotient indicated that the trace elements did not present any risks for consumers except for sodium. High phosphorous content and high phosphorus–protein ratio were observed in all categories which had a harmful health effect, hence named “new cholesterol.” Conclusion: Based on the information, this study is the leading work that deeply investigated the chemical composition of the Egyptian luncheon classes, and the obtained data could be beneficial to update the nutritional knowledge used by dietitians and the responsible for nutrition assessment and surveillance by the government. Adv. Vet. Anim. Res., 7(2): 299-307, June 2020